Meningkatkan Hasil Belajar Matematika Materi Pecahan melalui Pembelajaran Berdiferensiasi Menggunakan Asesmen Diagnostik Siswa Kelas IV UPT SD Negeri 21 Bulukunyi Kab. Takalar - Nurhikma Nurhikma; Baharullah Baharullah; Andi Ardillah Wahyudi (Departement of Mathematics Education, 2024)
The main problem in this study is how to improve mathematics learning outcomes through Differentiated Learning Using Diagnostic Tests for fourth grade students of SDN.No. 21 Bulukunyi, Takalar Regency. This study aims to improve mathematics learning outcomes by implementing Differentiated Learning Using Diagnostic Tests for Fourth Grade Students of SDN.No. 21 Bulukunyi, Takalar Regency. This type of research is classroom action research (Classroom Action Research) which consists of two cycles where each cycle is carried out twice. The research procedure includes planning, implementing actions, observation and reflection. The subjects in this study were fourth grade students of SDN.No.21 Bulukunyi, Takalar Regency in the even semester of 2024/2025, with a total of 24 students, 14 male and 10 female. Data collection was carried out using learning outcome tests and observations. The data collected were analyzed using quantitative and qualitative analysis. The results showed that the average value of students' mathematics learning outcomes in cycle I was 72.49 from the ideal score that could be achieved, namely 100, in the low category. Cycle II obtained an average value of mathematics learning outcomes of 80.62 from the ideal score that could be achieved of 100, which is in the high category. Although there are still many things that need to be fixed, during the learning process from cycle I to cycle II there was a significant change in students' positive attitudes. Student responses were also stated as positive because student learning activities in cycle I had a percentage of implementation of 83.92% (very good) and student learning activities in cycle II had a percentage of implementation of 92.85% (very good). The application of differentiated learning using diagnostic tests can increase student activity in learning, and can help students to stay focused and alert in various learning situations that are occurring so that there is an increase in the completeness of learning outcomes.